2011
DOI: 10.1021/ja110715f
|View full text |Cite
|
Sign up to set email alerts
|

The Aggregation-Enhancing Huntingtin N-Terminus Is Helical in Amyloid Fibrils

Abstract: The 17-residue N-terminus (httNT) directly flanking the polyQ sequence in huntingtin (htt) N-terminal fragments plays a crucial role in initiating and accelerating the aggregation process that is associated with Huntington’s disease (HD) pathogenesis. Here we report on magic-angle-spinning solid state NMR studies of the amyloid-like aggregates of an htt N-terminal fragment. We find that the polyQ portion of this peptide exists in a rigid, dehydrated amyloid core that is structurally similar to simpler polyQ fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

46
388
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 168 publications
(448 citation statements)
references
References 66 publications
46
388
2
Order By: Relevance
“…S3). Notably, our results are consistent with recent solid state NMR studies showing that HTT N16 region remains ␣-helical even in the aggregates but display increased dynamics and water exposure (40). As summarized in Fig.…”
Section: Discussionsupporting
confidence: 92%
“…S3). Notably, our results are consistent with recent solid state NMR studies showing that HTT N16 region remains ␣-helical even in the aggregates but display increased dynamics and water exposure (40). As summarized in Fig.…”
Section: Discussionsupporting
confidence: 92%
“…Similarly, it also is possible that domain swapping occurs prior to nucleation, resulting in the assembly of native-like but transient oligomeric aggregates. Note that various oligomeric assemblies of amyloidogenic proteins feature ␣-helical or native-like structures (66,67) that typically, but not always (68), are lost during fibril maturation.…”
Section: Discussionmentioning
confidence: 99%
“…Structural characterization of the aggregates (13,14,(18)(19)(20) has shown that, even when there are flanking sequences, polyQ remains the fiber core and adopts a β-hairpin conformation. In this paper, we use energy landscape analysis to provide a detailed molecular picture of the aggregation process of the peptide encoded by HTT exon 1, focusing on how the flanking sequences influence aggregation.…”
mentioning
confidence: 99%
“…Using the associative memory, water-mediated interactions, structure and energy model (AWSEM), previous simulations by our group have successfully explained how the change of critical nucleus size arises from the differences in the propensity of monomeric polyQ repeats of different lengths to form β-hairpins: the longer repeats fold into hairpins intramolecularly before they aggregate (9). The aggregation of the diseasecausing peptide is, however, further complicated by the presence of flanking amino acid sequences in fragments encoded by HTT exon 1. Experiments indicate that the addition of NT17 at the N terminus of polyQ enormously accelerates the aggregation, probably by encouraging the formation of prefibrillar oligomers (10)(11)(12)(13)(14)(15)(16), whereas the addition of the proline-rich region at the C terminus decreases the rate of aggregation apparently without changing fundamentally the mechanism (10,16,17). Structural characterization of the aggregates (13,14,(18)(19)(20) has shown that, even when there are flanking sequences, polyQ remains the fiber core and adopts a β-hairpin conformation.…”
mentioning
confidence: 99%